Molecular Mechanism of SARS-CoVs Orf6 Targeting the Rae1–Nup98 Complex to Compete With mRNA Nuclear Export - Li, Tinghan; Wen, Yibo; Guo, Hangtian; Yang, Tingting; Yang, Haitao; Ji, Xiaoyun (Frontiers in Molecular Biosciences, 2022)
The accessory protein Orf6 is uniquely expressed in sarbecoviruses including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which is an ongoing pandemic. SARS-CoV-2 Orf6 antagonizes host interferon signaling by inhibition of mRNA nuclear export through its interactions with ribonucleic acid export 1 (Rae1)–nucleoporin 98 (Nup98) complex. Here we confirmed the direct tight binding of Orf6 to the Rae1-Nup98 complex, which competitively inhibits the RNA binding. We determined the crystal structures of both SARS-CoV-2 and SARS-CoV-1 Orf6 C-termini in complex with the Rae1–Nup98 heterodimer. In each structure, SARS-CoV Orf6 occupies the same potential mRNA-binding groove of Rae1–Nup98 complex, comparable to the previously reported structures of other viral proteins complexed with Rae1-Nup98, indicating that the Rae1–Nup98 complex is a common target for different viruses to impair the nuclear export pathway. Structural analysis and biochemical studies highlight the critical role of the highly conserved methionine (M58) of SARS-CoVs Orf6. Altogether our data unravel a mechanistic understanding of SARS-CoVs Orf6 targeting the mRNA-binding site of Rae1–Nup98 complex to compete with nuclear export of host mRNA, which further emphasizes that Orf6 is a critical virulence factor of SARS-CoVs.